Music in the Mirror: Reflections on the History of Music Theory and Literature for the Twenty-First Century - Giger, Andreas -1965; Mathiesen, Thomas J. (Lincoln, NE University of Nebraska, 2002)
In Music in the Mirror, thirteen distinguished scholars explore the concept of music, music theory, and music literature as mirror images of one another - whether real or distorted. Encompassing the history of music and music theory and literature from the Middle Ages to the present, these essays, in their reconsideration of the relationships among music, theory, and literature, offer new approaches and articulate compelling visions for future research.
Keywords: Artistic research; Music theory; Music history; Music philosophy and esthetics